2011
DOI: 10.1109/tap.2011.2143688
|View full text |Cite
|
Sign up to set email alerts
|

Physical Bounds and Sum Rules for High-Impedance Surfaces

Abstract: High-impedance surfaces are articial surfaces synthesized from periodic structures. The high impedance is useful as it does not short circuit electric currents and reects electric elds without phase shift. Here, a sum rule is presented that relates frequency intervals having high impedance with the thickness of the structure. The sum rule is used to derive physical bounds on the bandwidth for high-impedance surfaces composed by periodic structures above a perfectly conducting ground plane. Numerical examples a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 25 publications
0
41
0
Order By: Relevance
“…Considerations about directivity limitations of antennas are presented in [78]. Bandwidth limitations for infinite array antennas are analyzed in [21,22,75] using the results in [49,94], see Sec. 7.…”
Section: Background and Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Considerations about directivity limitations of antennas are presented in [78]. Bandwidth limitations for infinite array antennas are analyzed in [21,22,75] using the results in [49,94], see Sec. 7.…”
Section: Background and Overviewmentioning
confidence: 99%
“…Here, the low-frequency expansion from [49] is used to extend the results to periodic structures. The sum rule is transformed to the bandwidth bound [22,75,94] [43,44,45] is labeled "100 %".…”
Section: Periodic Array Antennasmentioning
confidence: 99%
“…Sum rules have been used to derive physical bounds on electromagnetic systems such as matching [23], radar absorbers and array antennas [22,75,94], antennas [33,43,44], scattering [34,103], high-impedance surfaces [49], and metamaterials [41,52,104]. The sum rules are integral identities that often relate the parameter of interest integrated over all frequencies with some low-frequency quantity.…”
Section: Sum Rulesmentioning
confidence: 99%
“…Specic issues addressed are e.g. radar absorbers [32], high-impedance surfaces [8,18] and metamaterials [13]. Various antenna limitations have received considerable attention recently (a review can be found in the book by Volakis et al [39]).…”
Section: Introductionmentioning
confidence: 99%